Successful Treatment of Lomentospora Prolificans Infection Following Allogeneic Hematopoietic Stem Cell Transplantation: A Case Report and Literature Review - Yang YH; Di C; Zheng H; Luo Y; Zhang AR; Su T; Mo XD; Sun YQ; Wang Y; Lv M (Infection and Drug Resistance, 2025)
Yi-Han Yang,1,* Chun Di,2,* Hao Zheng,1 Ya Luo,1 Ao-Ran Zhang,1 Tong Su,1 Xiao-Dong Mo,1 Yu-Qian Sun,1 Yu Wang,1 Meng Lv1,3 1Peking University People’s Hospital, Peking University Institute of Hematology, National Clinical Research Center for Hematologic Disease, Beijing Key Laboratory of Cell and Gene Therapy for Hematologic Malignancies, Beijing, People’s Republic of China; 2Department of Clinical Laboratory, Peking University People’s Hospital, Beijing, People’s Republic of China; 3Clinical Trial Institution and Clinical Research Ward, Peking University People’s Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Meng Lv, Clinical Trial Institution and Clinical Research Ward, Peking University People’s Hospital, No. 11 Xizhimen South, Beijing, 100044, People’s Republic of China, Tel +86-10-88324637, Email drlvmeng@bjmu.edu.cnAbstract: Lomentospora prolificans is an opportunistic fungal pathogen known for its intrinsic multidrug resistance. This pathogen poses a significant challenge in immunocompromised individuals, particularly patients with hematologic malignancies. We present a case of a 27-year-old male diagnosed with adverse-risk acute myeloid leukemia (AML) who developed pulmonary Lomentospora prolificans infection following therapy for positive measurable residual disease (MRD) and severe chronic graft-versus-host disease (cGVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Despite the pathogen’s multidrug resistance and the typically poor prognosis associated with invasive infections in immunocompromised hosts, the patient achieved sustained remission and favorable outcome. This study systematically reviews Lomentospora prolificans infections following HSCT by analyzing 37 reported cases from 24 studies identified through a PubMed search. The majority of cases had acute myeloid leukemia as the most common underlying disease. Disseminated infections were predominant (83.8%), with frequent pulmonary and central nervous system involvement. Antifungal treatment strategies largely involved combination therapy, yet outcomes remained poor, with an overall survival rate of only 13.5%. These findings highlight the critical need for novel therapeutic approaches and early intervention strategies to improve patient outcomes.Keywords: hematopoietic stem cell transplantation, Lomentospora prolificans, terbinafine, voriconazole